Schaum's outline of mathematical methods for business and economics - Dowling, Edward Thomas , 1938- (Schaum's outlines series, 1993)
Schaum's Outline of Mathematical Methods for Business and Economics provides concise explanations illustrated by examples, plus numerous problems with fully worked-out solutions